Peran Lembaga Pendidikan Luar Sekolah Dalam Menanamkan Nilai Karakter Religius Anak Melalui Media Masjid Kelurahan Jalan Baru Curup - Abdul rahman; Erwin Syaputra; Mutiara Manata Sari; Neli Kusmita; Novi Novi (CV. ALIM'SPUBLISHING, 2024)
This research is motivated by the role of out-of-school educational institutions in instilling religious character values ​​in children through the medium of the Jalan Baru sub-district mosque. This research aims to meet children's needs in forming a religious character. This research uses a qualitative descriptive method, the techniques used in collecting data include (1) Observation, (2) interviews, (3) Documentation.Based on the results of this research, it can be concluded that the role of out-of-school educational institutions in instilling children's religious character values ​​through the mosque media in Jalan Baru sub-district: 1. What is the role of out-of-school educational institutions in instilling children's educational character values ​​through the media of the mosque in Jalan Baru Curup sub-district , The role of educational institutions in non-formal institutions at the Ukhuwah mosque is: a. Time management is time management in mosques which is important to ensure worship and other activities run smoothly and efficiently. 2. Collaboration with educators in instilling character values ​​in children's education through the medium of the mosque in the Jalan Baru Curup sub-district. At the ukhuwah mosque, cooperation has been carried out by children, namely in religious activities, students participate as lecturers, MCs, call to prayer, congregational prayers and mutual cooperation activities where community members voluntarily work together to carry out work or activities together for the common good.